Sintesis Nanopartikel Cerium Oxide Menggunakan Metode Presipitasi dan Sifat Optiknya - Nurhasanah, Iis; Sutanto, Heri; Muhlisin, Zaenul; Nurdianik, Sulistia; Nursanti, Ida (BERKALA FISIKA, 2012)
Cerium oxide nanoparticles have been synthesized using precipitation method in mixed-solvent system of aquades DM and isopropanol with volume rasio of 1:6.  Presipitation wascarried out by dropping amonium hidroxide to cerium nitrate hexahydrate solution until pH of 9. Precipitated was dried at temperature of 60oC for 2 hours and then calcined  for 2 hours attemperatur of 200oC, 300o and 400oC. Optical properties of cerium oxide nanoparticles werecharacterized using UV-Vis spectrophotometer. Cerium oxide nanoparticles exhibit goodtransparency in visible region and strong UV absorbance. These reults suggesting that ceriumoxide nanoparticles are potential as bionanomaterial for application in UV-blocker.Keywords: cerium oxide, nanoparticles, precipitation, UV filter, band gap energy, UV-Visspectrophotometer